Best-Friend Reports: A Tool for Measuring the Prevalence of Sensitive Behaviors - Yeatman, Sara (American Public Health Association, 2011)
We introduce the best-friend methodology for using surveys to measure the population prevalence of sensitive behaviors. We demonstrate the effectiveness of this tool by comparing self-reports to best-friend reports of sexual behavior and abortion history among young women in Malawi (n = 1493). Best-friend reports reveal higher and more believable estimates of abortion and multiple sexual partners. In contexts in which best friends commonly discuss such behaviors, best-friend reports are an inexpensive and easily implemented tool.